PENGARUH MUSIK TERHADAP KUALITAS TIDUR BAYI USIA 3-6 BULAN - Sri Ayu, Mayang; Yunita, Prasida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
Sleep is an unconscious condition where an individual can be awakened by a stimulus or sensory that is appropriate in other words, sleep is a state of relative unconsciousness not only a state of full activity, but more of a sequence of repeated cycles. Babies are children under one year of age who have just entered the early stages of life marked by rapid development. One of the factors that influences development in infants is rest or the length of sleep time. Babies with poor sleep quality have a negative impact on their development, such as babies becoming easily emotional and their concentration and immunity decreasing. This study aims to determine the effect of music on the sleep quality of infants aged 3-6 months. The research method is a quasi-experiment with a one group pre-test and post-test design. This research was conducted at the Tg. Balai Karimun Health Center, the sample in this study were 16 infants aged 3-6 months. The results of this study were obtained with an average value before 10.75 to 12.50 with a p-value of 0.000 (p <0.05) which means there is a significant difference between the pre-test and post-test scores, so it can be concluded that there is a difference in the average quality of sleep before and after music therapy. It is expected that mothers can provide care, especially classical music therapy as an alternative to improve sleep quality in infants. Keywords :Music Therapy, Baby Sleep Quality.